Solution processed 1D polymer/SWCNT composite arrays for high-performance field effect transistors. Issue 20 (11th May 2021) - Fan, Xiaoyu; Yang, Jingrun; Yang, Zhenghao; Lei, Bo; Che, Pengda; Gao, Hanfei; Liu, Yun; Feng, Jiangang; Wu, Yuchen; Jiang, Lei
Abstract : An integration technique has been developed to assemble the π-conjugated polymer/SWCNT composite materials into 1D arrays by exploiting an asymmetric-wettability assembly system, realizing enhanced charge-carrier mobility and thermal stability. Abstract : Semiconducting polythiophene polymers are promising materials for the generation of large-area and flexible electronics. However, the effect transistors (FETs) using semiconducting polymers as the channel material possess relatively poor mobility, which impedes their further applications. Conventional approaches, such as molecular structure design, micro-/nanostructure construction and processing-method optimization, suffer from the trade-offs between device performance, scalability, efficiency, and cost. Herein, we provide an alternative approach for integrating single-walled carbon nanotubes (SWCNTs) with polymers. The delocalized π plane of conjugated polymers and SWCNTs permits their self-assembly into co-axial structure with the SWCNT core and polymer shell driven by the π–π interaction. The polymer–SWCNT conjugated composites were further patterned into 1D arrays with regulated position, alignment and tunable size by controlling dewetting dynamics on an asymmetric-wettability template. Owing to the intrinsic high-efficiency carrier transport in SWCNTs and high degree of SWCNTs alignment, the PBTTT/SWCNT conjugated systems exhibit enhanced charge mobility of 1.47 cm 2 V −1 s −1, which is about 7 times higher than that of PBTTT. Furthermore, the incorporation of the high thermal conductive SWCNTs results in the enhanced thermal stability of PBTTT/SWCNTs.